Strategi Experiential Marketing dan Loyalitas Merek - Dian Tauriana; Rendy Manlin (Bina Nusantara University, 2008)
Consumer experience born from the consumption of a product or service gives a distinct impression in the minds of consumers. This impression creates brand loyalty, provided that the appropriate marketing program is designed to provide a unique experience. Article explores a study that uses primary and secondary data at Bengawan Solo Coffee to see the impact of marketing programs based on experience upon customer loyalty towards the Bengawan Solo Coffee brand. Data were collected by direct interviews of selected respondents through purposive sampling. Furthermore, those data were analyzed using several statistical methods, such as normality tests, the validity and reliability, the classic assumption test, Pearson product moment, and multiple regression. The results shows that there are significant correlation between marketing based on experience (feel, act, and relate) towards brand loyalty. The relationship between experiential marketing (feel and relate) towards brand loyalty is low, while the experiential marketing relationship (act) is quite strong.